IMPACT OF CLIMATE CHANGE AWARENESS ON CONSUMER PREFERENCES: A THEORETICAL ANALYSIS OF ECO-FRIENDLY MARKETING - Garg, Ankit Kumar; Singh, Chandan; Soni, Kartik; Singh, Shweta; Agrwal, Pranjal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the face of growing climate change awareness, consumer preferences are increasingly shifting toward eco-friendly products and services. This paper presents a theoretical analysis of how environmental consciousness impacts consumer behaviour and shapes the demand for sustainable alternatives. Drawing upon established consumer behaviour models and marketing theories, the paper examines the role of eco-friendly marketing strategies in influencing purchasing decisions. The analysis explores the effectiveness of green marketing, corporate social responsibility (CSR), and sustainability branding in meeting consumer expectations while highlighting the potential challenges, such as greenwashing and price sensitivity. The paper offers valuable insights for businesses seeking to align their marketing strategies with the rising demand for sustainability, contributing to the broader discourse on the role of corporate sustainability in the consumer market.